The Legal and Regulatory Framework for Environmental Impact Assessments : A Study of Selected Countries in Sub-Saharan Africa - Bekhechi, Mohammad A.; Mercier, Jean-Roger (Washington, DC: World Bank, 2013)
Environmental impact assessment, or EIA as it is known, is a procedures for evaluating the impact, proposed activities may have on the environment. In recent years, significant strides have been made to build a legal foundation for EIAs in Sub-Saharan Africa. Whereas EIAs typically used to be carried out only to meet requirements of foreign donors, they are now mandated in twenty two Sub-Saharan countries, as an important element of domestic environmental law, and policy. This publication traces the development of EIA, both in terms of national policies, and international law, and, analyzes EIA-related laws and regulations in those countries. The substantive components of EIA requirements, as well as the similarities, and differences of the various national statutes, are noted and commented upon. Special attention is paid to the role, and degree of public participation, for the further development of law, and policy with respect to environmental impact assessments in Sub-Saharan Africa.